An analysis of geometrical models for evaluating the influence of feed rate on the roughness of dry turned UNS A92050 (Al-Cu-Li) alloy. Issue 4 (1st October 2016) - Salguero, J.; Puerta, F. J.; Gomez-Parra, A.; Trujillo, F. J.; Sevilla, L.; Marcos, M.
Abstract: In this work, the results of a preliminary study on the dry turning of the UNS A92050-T84 alloy (Al–Cu–Li, third generation of Al–Li alloys) are shown. This study has been focused on the analysis of the final surface quality of the machined workpieces, in terms of average roughness ( R a ). Dry turning tests have been performed, using symmetric WC-Co cutting-tools, with different feeds and cutting speeds. Two different geometrical models, linear and quadratic, have been proposed, together with a non-geometrical potential model, obtained by adjusting the measurements to empirical data. Although the linear geometrical model is far from the acquired data, this model is formally similar to the parametric model, in which the feed exponent is close to one. This model allows predicting roughness theoretically for similar range of cutting conditions.